Advancing Competitive Positioning in The Photovoltaic Module Market with System Thinking: A Case of PT. Indonesia Solar Global - Zaeny Ahmad; Utomo Sarjono Putro (RSF Press, 2024)
Facing intense global competition and evolving regulatory challenges, the photovoltaic (PV) module market demands innovative strategies for competitive positioning, which this study addresses by applying systems thinking to uncover and analyze the complex interdependencies within the industry. Utilizing qualitative methods, the study engages key stakeholders through semi-structured interviews and employs Causal Loop Diagrams (CLDs) to ensure a rigorous and reliable analysis of the strategic and operational factors impacting PT. Indonesia Solar Global (ISG) within the PV module market. This study introduces a novel application of systems thinking to the photovoltaic module market, revealing how it can strategically enhance competitive positioning and operational efficiency, thus offering significant theoretical and practical contributions to the field of strategic management within renewable energy sectors. The findings reveal those strategic applications of systems thinking enable ISG to navigate complex market dynamics effectively, optimizing production efficiencies and enhancing competitive strategies against global competitors. This study not only addresses ISG's immediate challenges but also contributes to the broader discourse on strategic management within the renewable energy sector, showcasing the practical application of systems thinking in resolving industry-specific issues.